Dynamic Motion Control of Two-Link Robots with Adaptive Synergetic Algorithms - Abbas, Aya Khudhair; Kadhim, Saleem Khalefa (Journal of Robotics and Control (JRC), 2024)
Robotics is advancing to assist with daily tasks by developing human-like robotic limbs, which involves challenges in integrating software, control systems, electronics, and mechanical designs. To address these challenges, Classic Synergetic Controller (CSC) and Adaptive Synergetic Controller (ASC) algorithms were created using mathematical equations to regulate the robot arm's joint angle position and achieve precise tracking. A comparison with Adaptive Sliding Mode Control (ASMC) and Classical Sliding Mode Control (CSMC) demonstrated that CSC and ASC outperform in efficiency and robustness. ASC improved by 63%, providing smoother angular position tracking and faster response times. CSC reached the desired position angle in 1.5 seconds with oscillations, while ASC achieved it in 2.4 seconds without oscillations and eliminated chattering. CSC's Root Mean Square (RMS) was 1.57 rad, whereas ASC had no RMS value. The improvement rate of ASC over CSC was 100%, ensuring seamless motion, better rise time, and eliminating oscillations, thus providing robust control against disturbances and parameter variations.